If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 8 = 2x + 5 Reorder the terms: 8 + -2x = 2x + 5 Reorder the terms: 8 + -2x = 5 + 2x Solving 8 + -2x = 5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 8 + -2x + -2x = 5 + 2x + -2x Combine like terms: -2x + -2x = -4x 8 + -4x = 5 + 2x + -2x Combine like terms: 2x + -2x = 0 8 + -4x = 5 + 0 8 + -4x = 5 Add '-8' to each side of the equation. 8 + -8 + -4x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + -4x = 5 + -8 -4x = 5 + -8 Combine like terms: 5 + -8 = -3 -4x = -3 Divide each side by '-4'. x = 0.75 Simplifying x = 0.75
| 1+2(-2+2s)=-3+4s | | 7h-12=3h-5 | | -2(n+4)-4n= | | 1+2t=-3+4s | | 6x+2=78 | | -10=t-3 | | 23=-10(z-92)+73 | | -2k^5+8k^4= | | 8=2(6)-4 | | 8(x+y)+2x+3= | | 2(4z+2)-8=60 | | 3+6h=2h+14 | | X/5-8=3 | | (x-5)/10=10/3 | | 6x+10=31 | | (y+12)+(y-18)=180 | | 15.4+d=23 | | -4y-6=-3y-8 | | 8x=6(x-1) | | 565.2=1/3.22/7.6.6.h | | 8x^2+44x+60= | | 5x+4=46-2x | | 7+3=-5(3x-2) | | 7-2h=15-5h | | 45/w=5 | | 6x+100=10x-8 | | 1/4(11-8)=3/4 | | -8(2t+9)=-72 | | -8(2t+9)=-72t | | -5(f-67)+74=-1 | | 3m+4=7-3m | | 0=3x^3-12 |